KEPUASAN PENYEWA TERHADAP FAKTOR-FAKTOR PEMILIHAN KANTOR SEWA KELAS A FUNGSI MAJEMUK DI SURABAYA - Antusias Nurzukhrufa; Purwanita Setijanti; Asri Dinapradipta (Jurnal Arsitektur ARCADE, 2019)
Abstract: The growth of the supply and demand index of rental offices in Surabaya is the highest in Indonesia. However, the occupancy rate has decreased except in class A rental offices. Decrease in occupancy rate is influenced by dissatisfaction of tenants to the high rental price factor and causes the tenant not to extend the rent. The quality services of class A rental offices multifunction in Surabaya can be considered successful because the tenants have persisted in extending the leases. Therefore, it is necessary to know about the level of satisfaction of tenants to the factors that influence the choosing of class A rental offices multifunction in Surabaya. This research is included in the positivism paradigm with quantitative methods. The analysis technique uses quantitative descriptive statistics by calculating the mean and standard deviations mapped to the Cartesian diagram. This research results two findings. First, the three most satisfied factors i.e. "name of the famous building and its reputation is good", "responsive building management" and "the presence of good security, hygiene and fire protection facilities". Second, three factors that are most dissatisfied i.e. "access to recreational and sports facilities", "noise level" and "building age".Keyword: Rental Offices, Tenants Satisfaction, Real EstateAbstrak: Pertumbuhan indeks supply dan demand kantor sewa di Surabaya termasuk paling tinggi di Indonesia. Namun, tingkat okupansinya mengalami penurunan kecuali pada kantor kelas A. Penurunan tingkat okupansi dipengaruhi oleh ketidakpuasan penyewa terhadap faktor harga sewa yang tinggi dan menyebabkan penyewa tidak memperpanjang sewa. Kualitas layanan kantor sewa kelas A fungsi majemuk di Surabaya dinilai berhasil karena penyewa tetap bertahan untuk memperpanjang sewa. Maka, perlu diketahui tingkat kepuasan penyewa terhadap faktor-faktor pemilihan kantor sewa kelas A fungsi majemuk di Surabaya. Penelitian ini termasuk dalam paradigma positivisme dengan metode kuantitatif. Teknik analisis menggunakan statistik deskriptif kuantitatif dengan menghitung nilai mean dan standar deviasi yang dipetakan ke diagram kartesius. Penelitian ini menghasilkan dua temuan. Pertama, tiga faktor paling puas yaitu “nama gedung terkenal dan reputasinya baik”, “pengelola gedung yang responsif” serta “keberadaan fasilitas keamanan, kebersihan dan perlindungan kebakaran yang baik”. Kedua, tiga faktor paling tidak puas yaitu “kedekatan dengan fasilitas rekreasi dan olahraga”, “tingkat kebisingan” dan “usia gedung”.Kata Kunci: Kantor Sewa, Kepuasan Penyewa, Real Estate